Structural stability, electronic and magnetic properties of MoS2 quantum dots based on the first principles - Pei, Liang; Tao, Shen; Haibo, Shu; Song, Xing (Solid state communications, 2015)
The properties of MoS2 quantum dots are mainly ruled by the edge structures and shapes. We systematically explore structural stability, shapes and magnetic properties of different MoS2 quantum dots with different chemical potential of sulfur using the first principles. Three possible stable edge structures corresponding to different chemical potential of sulfur are confirmed. These edge structures are combined into different shapes of MoS2 quantum dots which is changed with sulfur chemical potential. The electronic structure calculation and the partial charge analysis indicate that the MoS2 quantum dot with armchair edge might have better catalyze ability. These MoS2 quantum dots show different magnetic behavior, which can adapt to different needs of spin devices. Given the recent achievement of graphene quantum dot structures and MoS2 quantum dots experimental study, we believe that our calculated results are suitable for experimental verification and can be useful to preparing different shapes of MoS2 quantum dots. •The Edge structures and shapes ruled properties of MoS2 quantum dots.•Three possible stable edge structures are combined into different shapes of MoS2 quantum dots.•MoS2 quantum dot with armchair edge might have better catalyze ability.